Liberação de mitomicina C - Influência de diferentes materiais - Margatho Ramos, Tamara [UNESP]; Silva, Maria Rosa Bet de Moraes [UNESP] (My University, 2003)
Purpose: To evaluate the quantity of Mitomycin C discharged from different materials with the same size, potentially used in the application of this medicine accessible in the surgery center of an Universitarian Hospital. Material and Method: It was studied 20 fragments with 5 to 5mm, from each 5 materials: Lyostypt, Weck sponge, absorbable cloth which is used to clean, cotton plate and of cotton swab concerning the saturation capacity and the quantity of mitomicyn discharged. In the first stage, it was studied the saturation capacity from each material. In the second stage, it was applied 0,1 ml solution of Mitomicyn C (0,5 mg/ml) and it was measured the biggest discharge halo in the filter paper and the discharged quantity (the difference between the weight before and after the medicine discharge). Results: The absorveble capacity from each material varied from 0,144 ml (absorbable cloth) to 0,216 ml Weck sponge. The discharge of Mitomicyn C was varied too, the biggest was the cotton plate and absorbable cloth. The Weck sponge and the cotton (of cotton swab) discharges the same quantity. Conclusion: The different materials discharged different quantities of Mitomicyn C. This can explain the different results of the trabeculectomy with Mitomicyn C. The surveys must inform not only the material used to apply the mitomycin C but the volume used too. Because the same values of mitomycin C liberation, cotton may substitute Weck sponje in trabeculectomy.
Mitomycin C releasing - Influence of different materials
Keywords: collagen; mitomycin C; cotton; drug delivery system; drug release; materials; surgical sponge; textile; trabeculectomy